Design and simulation of GRIN objective lenses for an imaging fiber based speckle metrology system - Prasad, A. S. Guru (2018)
Gradient-Index (GRIN) lenses are characterized by its small diameter and length, enabling them to be an effective lens for an integrated probe based imaging system. For a speckle-based surface metrology system, the imaging lens plays an important role in deciding the statistical dimensions of the speckles. In such cases, the design and simulation of the lens system would be a key process to better the performance of the lensed imaging fiber probe. In this context, this paper focuses on the design of lensed fiber probes for a speckle-based surface metrological imaging system that can find intra cavity interrogation applications. Different optical properties of GRIN lenses and imaging fibers are considered while designing the final probe distal end to meet the targeted specifications. Singlet GRIN lens configuration is analyzed for a front view configuration and a parameter optimization has been carried out to obtain the specifications including the field-of-view, resolution, working distance and magnification.